Transcriptomic profiling of thymic dysregulation and viral tropism after neonatal roseolovirus infection - Belean, Andrei; Xue, Eden; Cisneros, Benjamin; Roberson, Elisha D. O.; Paley, Michael A.; Bigley, Tarin M. (Frontiers in Immunology, 2024)
Introduction: Herpesviruses, including the roseoloviruses, have been linked to autoimmune disease. The ubiquitous and chronic nature of these infections have made it difficult to establish a causal relationship between acute infection and subsequent development of autoimmunity. We have shown that murine roseolovirus (MRV), which is highly related to human roseoloviruses, induces thymic atrophy and disruption of central tolerance after neonatal infection. Moreover, neonatal MRV infection results in development of autoimmunity in adult mice, long after resolution of acute infection. This suggests that MRV induces durable immune dysregulation.In the current studies, we utilized single-cell RNA sequencing (scRNAseq) to study the tropism of MRV in the thymus and determine cellular processes in the thymus that were disrupted by neonatal MRV infection. We then utilized tropism data to establish a cell culture system.Results: Herein, we describe how MRV alters the thymic transcriptome during acute neonatal infection.We found that MRV infection resulted in major shifts in inflammatory, differentiation and cell cycle pathways in the infected thymus. We also observed shifts in the relative number of specific cell populations. Moreover, utilizing expression of late viral transcripts as a proxy of viral replication, we identified the cellular tropism of MRV in the thymus. This approach demonstrated that double negative, double positive, and CD4 single positive thymocytes, as well as medullary thymic epithelial cells were infected by MRV in vivo. Finally, by applying pseudotime analysis to viral transcripts, which we refer to as "pseudokinetics," we identified viral gene transcription patterns associated with specific cell types and infection status. We utilized this information to establish the first cell culture systems susceptible to MRV infection in vitro.Our research provides the first complete picture of roseolovirus tropism in the thymus after neonatal infection. Additionally, we identified major transcriptomic alterations in cell populations in the thymus during acute neonatal MRV infection. These studies offer important insight into the early events that occur after neonatal MRV infection that disrupt central tolerance and promote autoimmune disease.